Southern Democrats - Rae, Nicol C. (Oxford University Press, 1994)
This text analyzes southern Democrats as a force in American politics since the 1960s. Drawing on interviews with many southern politicians, it traces the history of the Democratic Party in the South from the erosion of their national influence in the early 1960s to Clinton's election in 1992.